The Influence of Perceived Usefulness , Price and Brand Trust on Consumer Satisfaction in the Indriver Application - Tri mutiara sakinah Tiara; Tri Mutiara Sakinah; iharman saragih (Journal Of Management Analytical and Solution (JoMAS), 2024)
This research aims to determine the influence of perceived usefulness, price and brand trus on consumer satisfaction with the Indriver application (case study of marketing concentration management study program students at Simalungun Pematangsiantar University).This research was obtained from management study economics students who used the InDriver application that perceived usefulness, price and brand support increased consumer satisfaction in using the application. The sample used was 90 users who had used the Indriver service application who live in Pematangsiantar City. This research uses associative descriptive. Researchers use associative descriptive methods because in this research they will test the relationship model between variables and describe the research object, and test hypotheses using multiple linear regression analysis to explain phenomena in the form of relationships between two or more variables. The research results found that perceived usefulness, price and brand truts have a positive and significant influence on consumer satisfaction, perceived usefulness has a positive and significant influence on consumer satisfaction, price has a positive influence on consumer satisfaction, brand truts has a positive and significant influence on consumer satisfaction .